Docker containers : build and deploy with Kubernetes, Flannel, Cockpit, and Atomic - Negus, Chris, 1957-; Henry, William (Negus live Linux series., 2016)
"Whether on your laptop or a remote cloud, Docker can transform how you create, test, deploy and manage your most critical applications. In Docker Containers, Christopher Negus helps you master Docker containerization from the ground up ... Writing for systems administrators, software developers, and technology enthusiasts, Negus touches on every aspect of working with Docker: setting up containerized applications, working with both individual and multiple containers, running containers in cloud environments, and developing containers"--Back cover.